2013
DOI: 10.1002/apj.1706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of direct contact steam condensation in structured packing

Abstract: An experimental study of direct contact steam condensation has been conducted at both atmospheric and vacuum pressure, in a pilot scale column filled with Tupac 125Y structured packing. The local volumetric heat transfer coefficient of condensation determined by thermal balance has been given. The influences of the vapor and liquid flow rate, liquid temperature and operation pressure have been investigated. An empirical correlation based on dimensionless numbers has been put forward and verified by various exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The preliminary direction for the analysis was deducted based on the results published in [8]. Namely, after verifying the results published therein using the described methods, it was found that the dependency between the real heat transfer coefficient and the heat transfer coefficient in liquid obtained by using the similarity theory and procedure [4] has the following form:…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The preliminary direction for the analysis was deducted based on the results published in [8]. Namely, after verifying the results published therein using the described methods, it was found that the dependency between the real heat transfer coefficient and the heat transfer coefficient in liquid obtained by using the similarity theory and procedure [4] has the following form:…”
Section: Resultsmentioning
confidence: 92%
“…The measured values reported in the aforementioned source were evaluated using the same criteria as the ones which the authors of this paper have applied to validate their own measurement values, and which are reported in the above text. This analysis revealed that the experimental measurements are of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Many experimental and theoretical works have been performed on steam-water direct contact condensation in the packed column. [4][5][6][7] Bharathan et al [4] developed a one-dimensional, steady-state model that captures the heat, mass, and momentum processes of steam-water direct contact condensation in the presence of non-condensable gases. Huang and Fair [5] performed a reasonable method to use the mass transfer data to predict the heat transfer coefficients with the heat/mass transfer analogy, depending on type of packed bed and flow rates.…”
Section: Irect Contact Condensation Occurs When Vapour Condensesmentioning
confidence: 99%
“…Huang and Fair [5] performed a reasonable method to use the mass transfer data to predict the heat transfer coefficients with the heat/mass transfer analogy, depending on type of packed bed and flow rates. Li et al [6] established an experimental setup for the investigation of heat transfer capacity of Tupac 125Y structured packing in steam-water direct contact condensation at both atmospheric and vacuum pressure. The results showed that condensation efficiency in vacuum was higher than that in the atmospheric pressure.…”
Section: Irect Contact Condensation Occurs When Vapour Condensesmentioning
confidence: 99%
See 1 more Smart Citation